2018
DOI: 10.1159/000493150
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Enucleation of Bladder Leiomyoma: A Series of Six Cases and Review of the Literature

Abstract: Objectives: To investigate the feasibility and initial surgical outcomes of transurethral enucleation for 6 patients with bladder leiomyoma. Materials: Six patients (mean age 50.2, range [34–67]) with bladder leiomyoma underwent transurethral enucleation. In each case, the resectoscope was inserted into the bladder. A resecting loop was used to incise the urothelium along the surgical margin of the bladder tumor, and a push was given through the resecting loop to further separate the tumor until it was shelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…7 However, since 2012 treatment options have expanded to include methods such as vaginal resection and transurethral enucleation. 6,8 Endoscopic management maximizes bladder preservation and should be the recommended surgical approach if feasible for bladder leiomyomas. Li et al described transurethral enucleation of these benign tumors in which, after initial circumferential incision around the tumor margin, the resectoscope loop is used to bluntly separate the tumor from the surrounding urothelium prior to segmental tumor resection.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, since 2012 treatment options have expanded to include methods such as vaginal resection and transurethral enucleation. 6,8 Endoscopic management maximizes bladder preservation and should be the recommended surgical approach if feasible for bladder leiomyomas. Li et al described transurethral enucleation of these benign tumors in which, after initial circumferential incision around the tumor margin, the resectoscope loop is used to bluntly separate the tumor from the surrounding urothelium prior to segmental tumor resection.…”
Section: Discussionmentioning
confidence: 99%
“…As recent studies have shown promise in establishing best practices for evaluation and management, we reviewed the related studies on the last five years between 2016 and 2021. To review the features of bladder leiomyoma such as symptoms, diagnosis tools, treatment and prognosis, a literature search of PubMed and the Web of Science was conducted, which included 22 cases of bladder leiomyomas in 17 publications as shown in Table 1 (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The symptoms vary according to the location of the tumor, and may even be asymptomatic (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Also, benign conditions such as lipomas, hamartomas or nephrogenic adenoma and malignant conditions such as urothelial carcinoma, adenocarcinoma or metastatic cancer of the urinary tract should be considered. Ultrasound is the first tool for suspected bladder leiomyoma due to the characteristic image of the mass protruding into the bladder cavity, especially in endovesical-type tumors (3). A smooth, homogenous, and hypoechoic mass in the bladder wall is observed in an ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leiomyoma patients could present with hematuria, bacteriuria, frequently urinary system infection, flank pain and obstructive or irritative urinary symptoms. However, they can also be incidentally diagnosed [10,11]. Silva-Ramos et al [12] performed a clinical study with 90 patients who had bladder leiomyoma and found that most frequent complaint of the patients was irritative urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%